A simple quantum voting scheme with multi-qubit entanglement - Peng Xue (Nature Portfolio, 2017)
Abstract We propose a simple quantum voting scenario with a set of pairs of particles in a multi-particle entangled state. This scenario is suitable for large scale general votings. We also provide a proof of security of our scheme against the most general type of attack by generalizing Shor and Preskill’s proof of security of the other schemes.